ANALISIS KESULITAN BELAJAR MATA KULIAH BIOLOGI UMUM PADA PROGRAM STUDI PENDIDIKAN MATEMATIKA UNIVERSITAS INDRAPRASTA PGRI di MASA PANDEMI - Idha Isnaningrum (Jurnal Ilmu Pendidikan dan Sosial, 2022)
In every teaching and learning process, it will never be separated from learning difficulties, especially during a pandemic like today. Teaching and learning activities in the General Biology course are not free from learning difficulties. This study aims to analyze how difficult it is for students of the UNINDRA mathematics education study program to study General Biology courses. This study uses descriptive qualitative research techniques, where this research method seeks in-depth answers about a phenomenon that is currently happening. From the evaluation results, it was found that around 40% of lecturers use Whatsapp in the teaching and learning process, 0% zoom meetings, 20% Google Classroom, and 10% google meet. In this study, students of the UNINDRA mathematics education study program experienced learning difficulties as seen from the indicators we observed; 90% of lecturers or teaching staff, 87% teaching aids, 65% building conditions, 75% curriculum, 70% lesson time, 75% discipline level, 69% motivation and 80% learning media.